Ciclo reproductor e índices de condición usados en Melongena corona (Mollusca: Gastropoda) - Zetina Zárate, Adriana I.; Aldana Aranda, Dalila; Brule, Thierry; Barqueiro Cárdenas, Erick (Revista de Biología Tropical, 2000)
Melongena corona bispinosa was studied in Yucatán, México (21°16' N, 89° 49' W) for a year. Males have reproductive peaks in February and December, and a post-copulation peak in June. Female peaks are in March and May, plus oviposition peaks in April and January. Males and females differ in the mean gonadosomic index (F= 13.79, p<0.05) but not in the dry tissue/shell weight (F= 0.0902, p<0.05), dry tissue and total weight (F= 0.2466, p<0.05) and dry tissue weighl/internal shell volume (F= 1.0565, p<0.05).